Comparison study between seven-level SVPWM and two-level SVPWM strategy in direct vector control of a DFIG-based wind energy conversion systems - Habib Benbouhenni (International Journal of Applied Power Engineering (IJAPE), 2020)
In this paper, we present a comparative study between two-level space vector pulse width modulation (SVPWM) and seven-level SVPWM strategy in direct vector control (DVC) of a doubly fed induction generator (DFIG) based wind energy conversion systems (WECSs). The feasibility and effectiveness of the two strategies are demonstrated by simulation results. The obtained results showed that, the proposed DVC strategy with Seven-level SVPWM technique have stator and rotor current with low harmonic distortion and low active and reactive powers ripples than two-level SVPWM strategy.